2018
DOI: 10.1103/physreve.98.032418
|View full text |Cite|
|
Sign up to set email alerts
|

Reaction-diffusion kinetics on lattice at the microscopic scale

Abstract: Lattice-based stochastic simulators are commonly used to study biological reaction-diffusion processes. Some of these schemes that are based on the reaction-diffusion master equation (RDME), can simulate for extended spatial and temporal scales but cannot directly account for the microscopic effects in the cell such as volume exclusion and diffusion-influenced reactions. Nonetheless, schemes based on the high-resolution microscopic lattice method (MLM) can directly simulate these effects by representing each f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 87 publications
2
42
0
Order By: Relevance
“…This walk interval is fixed and identical across all processes throughout the simulation procedure. With the above bimolecular reaction scheme, we have shown that the rebinding-time probability distribution of a reactive molecule pair on HCP lattice agrees well with continuum theory (see Section III.A of [43]). We have also verified the accuracy of the reaction rate coefficient and its time-dependent behavior by comparison to SCK theory.…”
Section: Parallelized Walk Eventsupporting
confidence: 66%
See 4 more Smart Citations
“…This walk interval is fixed and identical across all processes throughout the simulation procedure. With the above bimolecular reaction scheme, we have shown that the rebinding-time probability distribution of a reactive molecule pair on HCP lattice agrees well with continuum theory (see Section III.A of [43]). We have also verified the accuracy of the reaction rate coefficient and its time-dependent behavior by comparison to SCK theory.…”
Section: Parallelized Walk Eventsupporting
confidence: 66%
“…W ij captures the intrinsic reaction rate k ij of the pair according to the Smoluchowski-Collins-Kimball (SCK) model [54,55]. The accuracy and consistency of the bimolecular reaction on lattice in both activation-limited and diffusion-limited regimes have been verified [43,45]. To represent volume occupying molecules, a voxel can be occupied by a single molecule at any given time.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations